Simultaneous resection of the primary tumour and liver metastases after conversion chemotherapy versus standard therapy in pancreatic cancer with liver oligometastasis: protocol of a multicentre, prospective, randomised phase III control trial (CSPAC-1) - Jin Xu; Si Shi; Jie Hua; Miaoyan Wei; Xianjun Yu (BMJ Open)
Introduction Approximately 50% of pancreatic ductal adenocarcinoma (PDAC) patients are diagnosed with distant metastasis, especially liver metastasis. The current standard treatment for these stage IV patients is palliative chemotherapy. There is increasing agreement that synchronous PDAC and liver metastasis resection may benefit highly selected patients. Thus, the Chinese Study Group for Pancreatic Cancer (CSPAC)−1 trial is being launched to establish a strategy for selecting PDAC patients with liver oligometastases who may benefit from synchronous resection after conversion chemotherapy.Methods and analysis In this study, liver oligometastasis is defined as no more than three metastatic lesions irrespective of their distribution within the liver lobes. The trial contains two steps. In the first step, 1000 to 1200 needle biopsy-confirmed PDAC patients with liver oligometastases are eligible for inclusion. Candidates will receive first-line chemotherapy. The RECIST V.1.1 criteria combined with tumour markers will be applied to evaluate the tumour response to chemotherapy every two cycles. Pancreatic cancer and hepatic metastasis resectability will be identified by multidisciplinary teams. Approximately 300 patients who meet our criteria will enter the second step and be randomly assigned at a 1:1 ratio to simultaneous resection of the primary pancreatic cancer lesion and liver oligometastases if no extensive metastatic sites are found during surgery or standard chemotherapy. Postoperative chemotherapy is recommended, and regimen selection should be based on the preoperative chemotherapy regimen. The primary endpoint is real overall survival (from enrolment to death). This study was activated in July 2018 and is expected to complete accrual within 5 years.Ethics and dissemination This trial has been approved by the Clinical Research Ethics Committee of Fudan University Shanghai Cancer Centre. Written informed consent will be obtained from all participants. Serious adverse events will be reported. Trial results will be submitted for peer-reviewed publication.Trial registration number NCT03398291; Pre-results.